Clinical impact of tumor DNA repair expression and T-cell infiltration in breast cancers - Green, Andrew R.; Aleskandarany, Mohammed A.; Ali, Reem; Hodgson, Eleanor Grace; Atabani, Suha; De Souza, Karen; Ellis, Ian O.; Rakha, Emad; Madhusudan, Srinivasan (American Association for Cancer Research, 2017)
Impaired DNA repair drives mutagenicity, which increases neoantigen load and immunogenicity. We investigated the expression of proteins involved in the DNA damage response (ATM, Chk2), double-strand break repair (BRCA1, BLM, WRN, RECQL4, RECQL5, TOPO2A, DNA-PKcs, Ku70/Ku80), nucleotide excision repair (ERCC1), base excision repair (XRCC1, pol β, FEN1, PARP1), and immune responses (CD8, PD-1, PD-L1, FOXP3) in 1,269 breast cancers and validated our findings in an independent estrogen receptor-negative (ER-) cohort (n = 279). Patients with tumors that expressed low XRCC1, low ATM, and low BRCA1 were not only associated with high numbers of CD8+ tumor-infiltrating lymphocytes, but were also linked to higher grades, high proliferation indexes, presence of dedifferentiated cells, ER- cells, and poor survival (all P ≤ 0.01). PD-1+ or PD-L1+ breast cancers with low XRCC1 were also linked to an aggressive phenotype that was high grade, had high proliferation indexes, contained dedifferentiated cells and ER- (all with P values ≤ 0.01), and poor survival (P = 0.00021 and P = 0.00022, for PD-1+ and PD-L1+ cancers, respectively) including in an independent ER- validation cohort (P = 0.007 and P = 0.047, respectively). We conclude that the interplay between DNA repair, CD8, PD-L1, and PD-1 can promote aggressive tumor phenotypes. XRCC1-directed personalization of immune checkpoint inhibitor therapy may be feasible and warrants further investigation in breast cancer.